(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Determine patients’ care needs and psychology after surgery and find some factors related to the caring needs of postoperative patients at Gia Rai Medical Center, Bac Lieu city, in 2020. Subjects and research methods: A cross-sectional descriptive study was conducted in the medical center Gia Rai, Bac Lieu, in 2020. The toolkit was based on “Guidelines for nursing care for patients according to Circular 07/2011/TT of the Ministry of Health” and related research. Results and discussions: All patients needed postoperative care (100%). Patients worried after surgery accounted for 89.9%, and up to 79.8% feared pain when injecting drugs. The results of multivariable logistic regression analysis showed that have a relationship between the needs of social care and gender (OR= 2,3, p < 0,005) and ethnicity (p <0,05). The needs of physical care and gender (OR= 3, 7, p < 0,05). There was no relationship between the need for physical and mental care and the patient’s general characteristics (p> 0,05). Conclusions and recommendations: Patients were high anxiety and needed care post-operative. Therefore, the patient needs to be explained and educated more after post-operative. In addition, the female and Kinh patients should pay attention because their needs caring were higher than other groups.